2015
DOI: 10.13080/z-a.2015.102.015
|View full text |Cite
|
Sign up to set email alerts
|

Redroot pigweed as a host for Alternaria alternata – the causal agent of Alternaria leaf blight in potato

Abstract: The aim of the study was to establish whether the redroot pigweed (Amaranthus retroflexus L.), which is a common weed in potato crops can be a source of Alternaria alternata, the causal agent of Alternaria leaf blight, and to determine the genetic diversity of isolates of this pathogen infecting the weed and the potato cultivar tested. With the A. alternata isolates selected for genetic testing, homosporous cultures were obtained, from which DNA (deoxyribonucleic acid) was subsequently isolated. The genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
2
0
3
Order By: Relevance
“…The aggressiveness of A. dauci isolates has been studied extensively in different carrot cultivars and under various environmental conditions [Courtial et al 2018]. Grapefruit extract was effective in controlling Alternaria leaf blight during the growing season [Mazur and Nawrocki 2007b]. Töfoli et al [2019] demonstrated that fluxapyroxad + pyraclostrobin and pyraclostrobin + metiram were more effective in controlling Alternaria leaf blight than boscalid + kresoxim-methyl, copper hydroxide and azoxystrobin.…”
Section: Resultsmentioning
confidence: 99%
“…The aggressiveness of A. dauci isolates has been studied extensively in different carrot cultivars and under various environmental conditions [Courtial et al 2018]. Grapefruit extract was effective in controlling Alternaria leaf blight during the growing season [Mazur and Nawrocki 2007b]. Töfoli et al [2019] demonstrated that fluxapyroxad + pyraclostrobin and pyraclostrobin + metiram were more effective in controlling Alternaria leaf blight than boscalid + kresoxim-methyl, copper hydroxide and azoxystrobin.…”
Section: Resultsmentioning
confidence: 99%
“…The problem of fungal diseases on ornamental plants has become increasingly important in recent years due to the growing frequency of their occurrence and the growing extent of injuries they cause from year to year. The importance of the fungus A. alternata as a pathogen in Poland is all the greater because it finds here favourable climatic conditions for its development (Mazur et al, 2015). Based on the results of the field experiment, the mycorrhizal inocula were found to have a positive effect on the growth, development and health of shrubs.…”
Section: Resultsmentioning
confidence: 99%
“…В работах, посвященных патогенам в грибных сообществах филлосферы и клубней картофеля, грибы рода Alternaria обнаруживаются на пораженных растениях в существенных количествах, однако стоит отметить, что в основном авторы используют метод культивирования изолятов, выращенных на специальных питательных средах (12,17,18). Исследования эндофитной микобиоты здорового растения, основанные на этом подходе, также подтверждают значительное присутствие грибов рода Alternaria (13).…”
Section: доля патогенов в сообществах грибов и грибоподобных организмunclassified
“…Альтернариоз и фитофтороз распространены во всех картофелеводческих регионах, проблемой борьбы с ними занимаются ученые в России и за рубежом. В частности, известны исследования филлопланы (3,12), эндофитных (13,14) и почвенных грибных сообществ (15,16), а также непосредственно участков растений, пораженных микозами (17,18); в результате были обнаружены возбудители фитофтороза, альтернариоза и других микологических заболеваний. Активно изучается воздействие на патогены различных агротехнических методов (15) и фунгицидов (8,10,19), которые могут использоваться в комбинации с другими средствами борьбы (20), например совместно с культуральной жидкостью бактерии Klebsiella planticola (21).…”
unclassified